What do we see from our window regarding of literaty readig by black authors? The already and the not yet (Revista Crioula, 2023)
This article reflects on the arena where readers and non-readers are located in Brazil. From the Bakhtinian perspective, we will weave dialogues with the work Da Minha Janela (2019), by Otávio Júnior, and illustration by Vanina Starkoff, through the reading strategies advocated by Girotto and Souza (2010), providing opportunities for connections in the production of meanings to the reader, in particular, with the entry into black-Brazilian literature, in order to ask questions and answer others.